P01.120 Importance of systematic TERT promoter and IDH mutations screening in non-diagnostic biopsies from patients​ with a suspected glioma. (19th September 2018) - Barritault, M; Picart, T; Poncet, D; Fenouil, T; Guyotat, J; Jouanneau, E; Joubert, B; Vasiljevic, A; Honnorat, J; Meyronet, D; Ducray, F
Abstract: Background: Non-diagnostic biopsies are a recurrent issue in patients with a suspected brain tumor. Herein, in order to explore the utility of molecular testing in this setting, we determined whether IDH and TERT promoter ( pTERT ) mutations can be detected in non-diagnostic biopsies from glioma patients. Material and Methods: Using Snapshot PCR, we retrospectively assessed IDH and pTERT mutation status in 28 adult glioma patients in whom a first non-diagnostic biopsy had led to perform a second biopsy. Results: Median age at diagnosis was 65 years and median delay between the first and second biopsy 21 days. The first biopsy consisted of non characterizable infiltrated glial cells (n=19), hemorrhage (n=4), necrosis (n=2) or normal tissue (n=3). The second biopsy demonstrated an IDH -wildtype glioblastoma (n=22), an IDH -wildtype astrocytoma (n=4), an IDH -mutant oligodendroglioma (n=1) and an IDH -mutant astrocytoma (n=1). A pTERT mutation was present in 21 cases. Retrospectively, the same IDH and pTERT mutations were identified in the non-diagnostic biopsies of the 2 patients with an IDH -mutant glioma and of 12 out of 21 patients with a pTERT -mutant glioma (57%). Overall an IDH and/or a pTERT mutation were detected in the non-diagnostic biopsies of 13 out of the 22 IDH -mutant and/or pTERT -mutant gliomas (59%) and in 13 out of the 28 cases included in the present series (46%). Conclusion: IDH and pTERT mutations can be detected in a high percentage of non-diagnostic biopsies from glioma patients supporting a role for molecular testing in the interpretation of non-diagnostic biopsies from patients with a suspected brain tumor